Tantangan Teknologi Informasi Perspektif Hukum Islam - R, Riska; Nurhadi, Ativa; Gassing, Qadir (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In this research, the researcher is interested in examining the challenges, impacts and perspectives of Islamic law on information technology challenges. The author uses a normative legal research methodology and a sharia approach. The author concludes that there are many challenges in information technology with the emergence of content that is wrong or not in accordance with Islamic teachings. Content like this can confuse Muslims and can even spread wrong understanding about the Islamic religion. The impact of this technological development is quite diverse, one side of life becomes easier, but on the other side it is harmed. There are many aspects that must be considered due to the impact of the use of information technology, especially on the morality and morals of the younger generation of Muslims. Muslims are expected to have a foundation, namely the teachings of Islam itself. At the same time, to face challenges, foundation, motivation, inspiration and faith are also needed. Here it is necessary to strengthen and strengthen the foundations of life in order to be able to face threats and avoid the detrimental aspects of the great battle of information technology. Therefore, it is necessary to pay attention and raise awareness again about the purpose of life according to Islam and to be responsible for actions in this world and their consequences in the afterlife.